Mechanochemical approaches towards the in situ confinement of 5-FU anti-cancer drug within MIL-100 (Fe) metal–organic framework - Souza, BE; Tan, J-C (Royal Society of Chemistry, 2020)
We elucidate two annealing assisted mechanochemical methods to achieve one-pot encapsulation of anti-cancer drug 5-fluorouracil (5-FU) in the iron-based MIL-100 metal–organic framework (MOF). We compare the structural and physicochemical properties of drug@MIL-100 systems derived from in situ manual and vortex grinding, where the former technique exhibits a slower drug release due to stronger guest–host interactions.